PENGARUH METODE PEMBERIAN RANSUM PADA SIANG DAN MALAM HARI TERHADAP BOBOT HIDUP, BOBOT KARKAS, DAN GIBLET AYAM JANTAN TIPE MEDIUM DIKANDANG POSTAL - Angga Prasetyo Kurniawan; Khaira Nova; Dian Septinova; Rr Riyanti (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This study aimed to investigate the effect of the percentage of day and night rations on live weight, carcass weight, and giblet weight of medium type roosters in postal cages. This study used a completely randomized design (CRD), consisting of three treatments with six replications, namely P1: giving rations of 30% day and 70% night, P2: giving rations of 50% day and 50% night, P3: giving rations 70 % day and 30% night. The data were analyzed using analysis of variance at the 5% level. The results showed that the percentage of different day and night rations had no significant effect (P> 0.05) on live weight (694.33 to 699.67 g / head), carcass weight (405.67 to 407.50 g / head), and giblet weight (35.67 to 36.83 g / head). However, the percentage of 30% day and 70% night rations tended to have the best effect on the lowest giblet weight, namely 35.67 g / head for the 7 week old medium type rooster. Keywords: Day and night percentage, Giblet, Rooster, Carcass weight, Live weight